Identification of most motivating resource for estimation of social hierarchy in water buffaloes - Sunil Dutt; M.L. Kamboj (Revista Científica)
Buffaloes are social animals and live in herds in natural settings. Under husbandry conditions, they are loosely housed in groups to allow them to express social behavior. The con struction of social hierarchy and knowledge of its determinants is warranted for determining the optimum group size and formulating strategies for shifting animals from one group to another. Social hierarchy is typically estimated by recording agonistic interactions among all animals for possession of limited resources. This study aimed to find the most limiting resource for estimating social hierarchy in riverine buffaloes. The study was conducted on 63 loose-housed (covered area=250m 2 ; open area=500m 2 ) with lactating Murrah buffaloes (BCS=3.25±0.16; 1-6 parity) maintained at ICAR-National Dairy Research Institute, Karnal, Haryana, India. Three limited resources considered for observing agonistic interactions were: i) seasonal green fodders, ii) concentrate mixture, and iii) possession of space under the foggers during the summer season (11:00, 07:00, and 14:00 hours, respectively). The manger length was restricted to allow 10% (length x width: 4.0 x 0.6 m) of animals to eat simultaneously, and 10% of foggers (3.7 m 2 space for two foggers) were operated to invite maximum aggression. Each restriction was carried out once daily in the same group. Access to resources was allowed from 10 m to ensure equal opportunity for possession. Agonistic interactions for each resource were recorded manually and by Closed Circuit Television recordings five times weekly by continuous sampling for 1 hour. A socio-metric matrix of all agonistic interactions was prepared, and pooled data was analyzed using one-way ANOVA in SPSS version 22. Participation of buffaloes for possession was higher (p<0.01) for the concentrate mixture (40.32±0.86%) compared to green fodders (25.08±0.66%) and foggers (12.38±1.80%). Several agonistic interactions were statically significant (p<0.01) for possession of concentrate (25.4±0.54), followed by green fodders (15.80±0.42) and foggers (7.80±1.13). The number of physical (fighting, bunting, pushing) and non-physical (threatening, avoiding) interactions were higher (p<0.01) for concentrate (439.4±13.49, 368.8±12.16) than green fodder (126.6±9.49, 147.8±90) and foggers (36.90±7.22, 83.5±6.61). We concluded that concentrate restriction motivates the expression of agonistic interactions for resource possession in socially stable lactating buffaloes.